Blood runs coal : the Yablonski murders and the battle for the United Mine Workers of America - Bradley, Mark A. (Mark Andrew), 1956- (W.W. Norton & Company, 2020)
"The shocking assassination of a major rival to UMWA president Tony Boyle catalyzed groundbreaking reform in the coal mining industry. In the early hours of New Year's Eve 1969, in the small soft-coal mining borough of Clarksville, Pennsylvania, longtime trade union insider Joseph "Jock" Yablonski and his wife and daughter were brutally murdered in their old stone farmhouse. Seven months earlier, Yablonski had announced his campaign to oust the corrupt president of the United Mine Workers of America (UMWA), Tony Boyle. Boyle had long embezzled UMWA funds, silenced intra-union dissent, and served the interests of Big Coal companies. He was enraged about his opponent's bid to take over. An extraordinary portrait of one of the nation's major unions on the brink of historical change, Blood Runs Coal comes at a time of resurgent labor movements in the United States and the current administration's attempts to bolster the fossil fuel industry. Brilliantly researched and compellingly written, it sheds light on the far-reaching effects of industrial and socioeconomic change that unfold across America to this day"--